Spatial and temporal variation in the distribution of the population of Wasit Governorate (using some statistical methods) for the period (1997 – 2020) - Abed, Qasim Mohammed (Al-Adab Journal, 2022)
The research aims to know the nature of the population distribution in Wasit Governorate and to reveal the temporal and spatial variation of that distribution in the period from (1997 - 2020). Such studies contribute to determining the type and amount of services provided to the population and the extent to which they meet the needs of the population in the same region. The research showed the centrality of the axis of population distribution and the axis of distribution metrics to a set of results, including that the population in Wasit Governorate is not distributed in a balanced manner in their administrative units, and there are some administrative units that account for the largest share of the population for economic and social reasons, and the study revealed that their use is more than Statistical method The governorate has tended in recent years towards a clear concentration in city centers and with riverbeds and with extensions of transportation routes.